Influência da idade do paciente nos resultados do clareamento dentário em consultório: Um ensaio clínico - Araujo, Isabela Sousa de (2019)
This study evaluated the impact of patients` age on tooth sensitivity (TS), the bleaching effectiveness following the in-office dental bleaching with hydrogen peroxide applied in three 15-min consecutive applications or in a single-application of 45 min, as well as the satisfaction of these patients after the procedure. Fifty-six participants were divided according to their age into younger (18 to 25 year-old) and older (40 to 65 year-old). A split-mouth design was used to evaluate the effectiveness of two the bleaching protocols. The upper incisors and canines were used to assess the bleaching effectiveness achieved with two sessions of bleaching (one-week interval). Color changes were assessed by a shade guide (Bleachedguide) and a portable spectrophotometer. Visual analogue (VAS) and verbal rating scales (VRS) were used to record tooth sensitivity during and up to 48 hours after the bleaching procedures. Psychosocial Impact of the Dental Esthetics Questionnaire (PIDAQ) was applied to evaluate satisfaction. Data were analyzed by Fisher`s Exact test, Mann-Whitney, Wilcoxon, Friedman, and 2- way Repeated Measures ANOVA (α = 0.05). There was no difference between the bleaching protocols regarding the level of TS. The participants` age affect the risk to TS only for a three 15-min consecutive applications of bleaching agent, with increased risk to younger patients. Lower level of TS was reported by the older ones. Regardless of the bleaching protocol, improved bleaching effect in both upper canines and incisors were obtained with younger participants. In conclusion, the patients` age impacted the outcomes of in-office bleaching, while improved color changes were observed for the teeth of the younger patients despite the increased level of TS reported by them. The aesthetic satisfaction was positive for both age groups, and the general perception of the psychosocial impact of dental aesthetics was greater observed by the older patients.